Polymorphous Low-Grade Adenocarcinoma: A Rare Cause of Long-term Epistaxis - Teng-Chin Wang; Yi-Tsung Yang; Ming-Tsun Tsai (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Polymorphous low-grade adenocarcinoma (PLGA) of the paranasal sinus is an extremely rareisease. PLGA is a minor salivary gland neoplasm that occurs mostly in the junction of the soft andhard palate, followed by the buccal mucosa and upper lip. Only a few cases have been reported in the sinonasal area. PLGA  generally follows a benign clinical course with frequent perineural invasion but low metastatic potential We report on a patient with PLGA in the ethmoid sinus, which presented as a nasal polyp withepistaxis for more than 2 years. The patient received surgical excision with adjuvant radiotherapy and chemotherapy because of perineural and lymphavascular invasion. One year after treatment,the patient was free of disease. PLGA of the paranasal sinus is an extremely rare disease. Epistaxis as the initial presentation is also uncommon. Local recurrences and distant metastasis are rare if complete excision is performed. Long-term follow-up is required.